Efficiency of fishing gears in the river Halda, Chittagong, Bangladesh - Mohammad Arshad-Ul-Alam; Mohammad Ali Azadi (Journal of Fisheries, 2015)
To determine the catch efficiency of fishing gears, catch per unit effort (CPUE) data were collected for two years during January 2007 to December 2008 from the river Halda. Analyses were done to examine the variation of CPUE among gears, studied sections, months and years. The mean CPUE for pooled data of all gears was 2.247±0.265 kg.gear-1day-1 and 2.697±0.355 kg.gear-1day-1 for 2007 and 2008 respectively. Among eight gear categories, bag nets yielded the highest CPUE during 2007 (5.957±0.704 kg.gear-1day-1) and seine nets during 2008 (7.288±1.477 kg.gear-1day-1). Among 31 gear types, small meshed bag nets yielded the highest CPUE (18.065±6.660 and 15.69±4.479 kg.gear-1day-1 during 2007 and 2008 respectively). CPUE was highest during March-April and September-November periods. Analysis of variance showed significant difference among catch rates of different fishing gears. The CPUE differed significantly among different months for net fence, gill net, cast net and scoop net during 2007; and for seine net, net fence, bag net and cast net during 2008.